DESIGN AND SYNTHESIS OF NEW HOMO- AND HETEROMETAL COORDINATION COMPOUNDS OF GERMANIUM(IV) FOR PREPARATION OF LOW TOXIC DRUGS WITH A WIDE THERAPEUTIC ACTION - I. I. Seifullina; E. E. Martsinko; E. V. Afanasenko (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
Coordination compounds of essential microelement germanium(IV) with metals (Mg, Na, K, Ca, Cu, etc.) and organic ligands – biocatalysts, antidotes at intoxications and regulators of mineral metabolism in living organism (nicotinic, citric, tartaric, 1-hydroxyethylidendiphosphonic acids, nicotinamide) are synthesized for the first time on the Department of General Chemistry and Polymers of Odessa Mechnikov National University. The favorable activity of the synthesized compounds on cardiovascular and chronic respiratory diseases, senile pneumonia, neuropsychiatric and metabolic disorders, ischemic heart diseases, etc. is described. Thus, the influence of 1-hydroxyethylidendiphosphonatogermanate (medgerm) on CNS, its anxiolytic activity and absence of both hypnotic and myorelaxant effects has been shown. Cardioprotector properties of magnesium hydroxyethylidendiphosphonategermanate as a potential effective and safe drug with the high antihypertensive and antiarrhythmic activity have been found out. The interferoninductive and immunostimulatory activity of germanium(IV) compounds with 1-hydroxyethylidendiphosphonic, nicotinic acids, nicotinamide, pyracetam has been studied. Injection of these drugs (concentration 100-125 μg/ml) causes the 100 % delay of cytopathic action of vesicular stomatitis virus in the cell cultures that demonstrates the ability of compounds to increase essentially cells stability. The perspectives of germanium coordination compounds as interferon inductors and as immune pharmaceuticals for prevention the disbalance of the immune system are reviewed.